InsteaDMatic: towards cross‐platform automated continuous rotation electron diffraction. Issue 5 (20th August 2020) - Roslova, Maria; Smeets, Stef; Wang, Bin; Thersleff, Thomas; Xu, Hongyi; Zou, Xiaodong
Abstract : A DigitalMicrograph script named InsteaDMatic has been developed for automated continuous rotation electron diffraction (cRED) data acquisition. InsteaDMatic coordinates functions of the transmission electron microscope goniometer and camera in order to tune up diffraction‐frame recording simultaneously with crystal rotation. Exploiting fast and automated data collection, the influence of the electron dose rate on the quality of cRED data was studied, and structural models obtained for two different parallel‐beam illumination modes (aperture selection and nanoprobe) were compared. Abstract : A DigitalMicrograph script, InsteaDMatic, has been developed to facilitate rapid automated 3D electron diffraction/microcrystal electron diffraction data acquisition by continuous rotation of a crystal with a constant speed, denoted as continuous rotation electron diffraction. The script coordinates microscope functions, such as stage rotation, and camera functions relevant for data collection, and stores the experiment metadata. The script is compatible with any microscope that can be controlled by DigitalMicrograph and has been tested on both JEOL and Thermo Fisher Scientific microscopes. A proof of concept has been performed through employing InsteaDMatic for data collection and structure determination of a ZSM‐5 zeolite. The influence of illumination settings and electron dose rate on the quality of diffraction data, unit‐cell determination and structure solution has been investigated in order to optimize the data acquisition procedure.